ETHICAL ENHANCEMENT ANALYSIS FOR ROYAL THAI ARMY EDUCATION DEPARTMENT PERSONNEL BASED ON (BRAHMAVIHARA IV): ETHICAL ENHANCEMENT ANALYSIS FOR ROYAL THAI ARMY EDUCATION DEPARTMENT PERSONNEL BASED ON (BRAHMAVIHARA IV) - Deelert, Panya (Mahachula Academic Journal, 2026)
This qualitative research entitled “An Analysis of Ethical Enhancement for Personnel of the Royal Thai Army Education Department Based on the Four Sublime States of Mind (Brahmavihāra IV)” aimed to achieve three primary objectives: 1) to examine the ethical principles of personnel in the Royal Thai Army Education Department according to Brahmavihāra IV; 2) to investigate the application of Brahmavihāra IV in enhancing personnel ethics; and 3) to analyze strategic guidelines for ethical enhancement within the department based on these four principles. Data were collected via in-depth interviews with twenty key informants, including commanding officers, military chaplains, and operational personnel of the Royal Thai Army Education Department. The gathered data were subsequently synthesized and analyzed using descriptive analysis. The research findings indicated that the current ethical promotion mechanism within the Royal Thai Army Education Department operates systematically through well-defined organizational structures, led by commanding officers and driven primarily by military chaplains through religious activities aligned with the fiscal year. Although this framework effectively maintains military discipline, it faces challenges regarding consistency and adaptability to modern societal transformations. Consequently, a paradigm shift is required, moving from conventional classroom-based instruction toward creating accessible, concrete, and experiential ethical learning. Furthermore, the application of Brahmavihāra IV plays a pivotal role in transforming ethical attitudes and behaviors. Loving-kindness (Mettā) and Compassion (Karuṇā) serve as foundations for fostering empathy and reducing mutual harm. Sympathetic Joy (Muditā) generates positive energy and mitigates organizational jealousy, while Equanimity (Upekkhā) functions as a key mechanism for maintaining military discipline and justice without bias. Internalizing these virtues (Attūpanāyika) shifts the paradigm from compliance by regulations to willingness through inherent morality, thereby enhancing personnel’s emotional and psychological resilience during missions. Crucially, effective guidelines for ethical enhancement entail integrating these Buddhist virtues into the human resource management system, emphasizing the "Ethical Leadership Model" where leaders embody Dhamma practices. This must operate in tandem with "Digital Buddhist Innovation" as a communication channel for the new generation of personnel. Harmonizing rigid administrative compliance with fraternal benevolence will ultimately transform ethics into a living practice, ensuring sustainable well-being and institutional success.